PENINGKATAN PROSES PEMBELAJARAN MELALUI IMPLEMENTASI ADMINISTRASI KELAS DI UPTD SDN 14 LAPONGKODA KECAMATAN TEMPE KABUPATEN WAJO - Amaliah, Fadillah Rezki; Besse Herlina; Darmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
UPTD SDN 14 Lapongkoda, Tempe District, Wajo Regency, an elementary school located at Jalan Batam No. 3 Sengkang. This study aims to analyze the implementation of class administration in improving the learning process and analyze the supporting and inhibiting factors of class administration in improving the learning process at UPTD SDN 14 Lapongkoda. The research method used is a qualitative approach with an exploratory research type with data collection techniques through interviews, observations, and documentation. The main data sources in this study include the principal and 4 class teachers (from grade III to grade VI). The results of the study indicate that there is an increase in the learning process through the implementation of class administration that is well planned and supported by adequate facilities, so that the learning process can run more effectively, efficiently, and sustainably so that the learning process can be achieved optimally. In addition, there are inhibiting factors in the implementation of class administration such as limited learning resources, limited classroom space, and inadequate facilities and infrastructure. These findings indicate that improving the learning process through the implementation of well-managed class administration is expected to run more effectively, efficiently, and meaningfully for students.